2021
DOI: 10.18632/aging.203230
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of m6A mRNA methylation in rats with monocrotaline-induced pulmonary arterial hypertension

Abstract: Background: N6-methyladenosine (m 6 A) modification is one of the most common chemical modifications of eukaryotic mRNAs, which play an important role in tumors and cardiovascular disease through regulating mRNA stability, splicing and translation. However, the changes of m 6 A mRNA and m 6 A-related enzymes in pulmonary arterial hypertension (PAH) remain largely unexplored. Methods: MeRIP-seq was used to identify m 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 57 publications
4
24
0
Order By: Relevance
“…Accordingly, YT521-B homology (YTH) domain family is the main “readers” ( Jones et al, 2022 ) and “erasers” consisting of FTO and ALKBH5 ( Kaur et al, 2022 ). Recent studies have focused on the importance of m6A modification in tumors ( Jiang et al, 2022 ; Ma et al, 2022 ; Xiong et al, 2022 ; Yadav et al, 2022 ) and non-neoplastic diseases like asthma and pulmonary hypertension ( Teng et al, 2021 ; Zeng et al, 2021 ; Zhou et al, 2021 ). Nevertheless, the expression pattern of m6A regulators in CHP and IPF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, YT521-B homology (YTH) domain family is the main “readers” ( Jones et al, 2022 ) and “erasers” consisting of FTO and ALKBH5 ( Kaur et al, 2022 ). Recent studies have focused on the importance of m6A modification in tumors ( Jiang et al, 2022 ; Ma et al, 2022 ; Xiong et al, 2022 ; Yadav et al, 2022 ) and non-neoplastic diseases like asthma and pulmonary hypertension ( Teng et al, 2021 ; Zeng et al, 2021 ; Zhou et al, 2021 ). Nevertheless, the expression pattern of m6A regulators in CHP and IPF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 78 , 80 No changes were observed in the expression of the majority of other m 6 A regulators, including METTL14, VIRMA, RBM15, YTHDF2-3, YTHDC1-2, or IGF2BP1-3. 78 Contrary to the above findings, lung tissue of rat pups with hypoxic pulmonary hypertension showed downregulated levels of m 6 A residues in RNAs, and decreased expression of METTL3, METTL14, FTO, and ALKBH5. 77 …”
Section: N 6 -Methyladenosine and A-to-i Modificat...mentioning
confidence: 95%
“…Figure 2 offers an overall summary of studies that have assessed either m 6 A or A-to-I RNA modifications in cardiovascular development, physiology, or disease. 50 , 54 , 55 , 56 , 57 , 58 , 54 , 55 , 56 , 57 , 58 , 68 , 67 , 66 , 65 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , …”
Section: N 6 -Methyladenosine and A-to-i Modificat...mentioning
confidence: 99%
“…Several studies have reported that m6A methylation levels are significantly upregulated in a rat model of pulmonary hypertension, and these differentially m6A methylated genes proved to be involved in inflammation, glycolysis, endothelial cell receptor activation, and lung development, which can accelerate the progress of pulmonary hypertension ( Xu et al, 2021 ; Zeng et al, 2021 ). Down-regulation of m6A modification by knockdown of METTL3 and METTL14 can delay the progression of pulmonary hypertension by inhibiting the proliferation and migration of pulmonary arterial smooth muscle cells ( Zhou X.-L. et al, 2021 ; Table 3 and Figure 2 ).…”
Section: M6a Methylation and Cvdsmentioning
confidence: 99%